Analysis of Modified Exhaust Tip Geometry on Flow Behavior and Backpressure in Car Exhaust Systems for Electricity Harvesting - Martias; Wawan Purwanto; Okin Johepan Handanu; Agus Baharudin; Andrizal (Advance Sustainable Science Engineering and Technology, 2025)
The efficiency of vehicle exhaust systems is critical for reducing backpressure and emissions, enhancing performance and sustainability of harvesting energy. This study investigates the effect of an additional body modification at the exhaust tip on pressure and velocity distributions using Computational Fluid Dynamics (CFD) simulations in SolidWorks. Simulations were conducted at inlet velocities of 10, 15, and 20 m/s. Results show that the modified design does not increase backpressure, with the maximum observed change being a minor reduction of 0.137% at 20 m/s. These findings confirm that the additional body can be safely integrated without adversely affecting engine performance, while also improving downstream flow uniformity. This supports its viability for use in energy harvesting systems and highlights its relevance for sustainable exhaust system development.